Measurement of the axial-vector τ spectral functions and determination of αs (M2τ) from hadronic τ decays - BARATE, R. (Institutional Knowledge at Singapore Management University, 1998)
An analysis based on 124 000 selected ττ pairs recorded by the ALEPH detector at LEP provides the vector (V)(V) and axial-vector (A)(A) spectral functions of hadronic ττ decays together with their total widths. This allows the evaluation of finite energy chiral sum rules that are weighted integrals over the (V−A)(V−A) spectral functions. In addition, a precise measurement of αsαs along with a determination of nonperturbative contributions at the ττ mass scale is performed. The experimentally and theoretically most robust determination of αs(M2τ)αs(Mτ2) is obtained from the (V+A)(V+A) fit that yields αs(M2τ)=0.334±0.022αs(Mτ2)=0.334±0.022 giving αs(M2Z)=0.1202±0.0027αs(MZ2)=0.1202±0.0027 after the extrapolation to the mass of the Z boson. The approach of the Operator Product Expansion (OPE) is tested experimentally studying the evolution of the ττ hadronic widths to masses smaller than the ττ mass.